Kajian terhadap Tanggungjawab Pengurus CV dan Nasib Buruh Terkait CV Dinyatakan Pailit - Sunur, Fransiskus Stefan; Sari, Retno Dewi Pulung (Wajah Hukum, 2024)
Bankruptcy is a situation where there is a Bankruptcy Decision against the Debtor from the Commercial Court. In the management of a limited partnership or CV, there are active partners and passive partners, both of which have different responsibilities. Then, in terms of the rights owned by workers, namely wages or salaries, Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations explains that there are three (3) types of Creditors, namely Separatist Creditors, Preferred Creditors, and Concurrent Creditors. Then, this research uses a normative research method with primary and secondary legal materials and collects data using literature studies using the snowball method to search for legal materials. The aim of this research is to examine the responsibilities of CV management and the fate of workers related to CV being declared bankrupt. Thus, the results of this research are that there are differences in the responsibilities of CV administrators in the event that a CV is declared bankrupt by the court between CV administrators who are active partners and passive partners. In addition, there is legal protection for workers' rights in the event of bankruptcy, namely the right to fair wages.